Concept of “Error” in Foreign-Language Speech of Students in Domestic and Foreign Theory and Practice - M. A. Kecherukova (Научный диалог, 2018)
The generalization of the main results in the field of research of the theory of error in foreign language speech of students and the implementation of these studies in the practice of teaching a foreign language is presented. The existing works, in which special attention is paid to the theory of error, are analyzed. The article considers how the interpretation of the concept of “error” changed depending on the dominant method of teaching a foreign language in a specific period (grammar-translation method, communicative-oriented learning). Various definitions of errors, causes, typologies of errors, methods of their prevention and correction are given. Particular attention is paid to the issue of language and linguocultural interference, socio-cultural error, as well as terminological differences in domestic and foreign studies on the theory of error. The author analyzes the collected empirical data, makes conclusions about the degree of implementation of the theory in the real practice of teaching a foreign language in high school. According to the author, the developed theory of errors in foreign language speech of students is not systematically used in real practice of teaching foreign languages. The inclusion of this topic in the curriculum of teacher training courses would undoubtedly contribute to the improvement of the quality of foreign language teaching.